2008
DOI: 10.1007/s00535-008-2158-9
|View full text |Cite
|
Sign up to set email alerts
|

Amylase levels in bile in patients with a morphologically normal pancreaticobiliary ductal arrangement

Abstract: Occult pancreaticobiliary reflux is observed in a considerable number of ERCP candidates. Those who show an extremely high biliary amylase level, at least, may be at high risk for biliary malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 13 publications
2
41
2
Order By: Relevance
“…Of note, it has been demonstrated that biliary amylase levels of 10,000 IU/L or higher can be detected in 6 and 10.8 % of patients with biliary tract malignancies and benign biliary tract disease, respectively [59]. Elsewhere, it has been proposed that even in individuals whose papillary sphincter does act on the pancreaticobiliary junction, biliary amylase levels may be elevated to mean values of 48,000 IU/L if their common channel is sufficiently long, although such levels are still lower than the mean values seen in patients with PBM [3].…”
Section: Commentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Of note, it has been demonstrated that biliary amylase levels of 10,000 IU/L or higher can be detected in 6 and 10.8 % of patients with biliary tract malignancies and benign biliary tract disease, respectively [59]. Elsewhere, it has been proposed that even in individuals whose papillary sphincter does act on the pancreaticobiliary junction, biliary amylase levels may be elevated to mean values of 48,000 IU/L if their common channel is sufficiently long, although such levels are still lower than the mean values seen in patients with PBM [3].…”
Section: Commentsmentioning
confidence: 98%
“…Therefore, an increase in the levels of amylase in the bile is strong evidence of pancreatobiliary reflux [2]. A level of biliary amylase distinctly above the normal upper limit has been used as a diagnostic criterion in different reports [26,58,59], including levels of 500 IU/L [60] and 1,000 IU/L or higher [61].…”
Section: Commentsmentioning
confidence: 99%
“…[5,8,13,15,16] Although, it is unclear whether the stones causes PBR or vice versa, our observation of PBR in patients with acute calculous cholangitis is compatible with the results of others that conducted studies on occult PBR in patients with a normal pancreatobiliary junction. [6,14] However, there is still no definitive knowledge of exactly what this occult PBR means clinically.…”
Section: Discussionmentioning
confidence: 99%
“…[6,8,13,14] Some researchers hypothesized that papillitis due to stones causes dysfunction of the sphincter of Oddi, which then leads to reflux of pancreatic juice. [14] In contrast, others suggested that reflux of pancreatic juice causes chronic inflammation of the gallbladder, which subsequently results in gallstone formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation